Contemporary cases in management: Perspectives from emerging markets - Aggarwal, Shalini; Gupta, Ashish (London Routledge, 2025)
Emerging markets due to their dynamism, resilience and complexities are a significant area of study for management theorists and practitioners. This volume brings together case studies from diverse corners of the industry and offers insightful analyses of real-world management challenges and strategies in dynamic environments.